Harvest trends, growth and longevity, and population dynamics reveal traditional assumptions for redhorse (Moxostoma spp.) management in Minnesota are not supported - Alec R. Lackmann; Ewelina S. Bielak-Lackmann; Reed I. Jacobson; Allen H. Andrews; Malcolm G. Butler; Mark E. Clark (Environmental Biology of Fishes, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Connection for conservation: The impact of counting butterflies on nature connectedness and wellbeing in citizen scientists - C.W. Butler; I. Hamlin; M. Richardson; M. Lowe; R. Fox (Biological Conservation, 2024)

Otolith allometry informs age and growth of long-lived Quillback Carpiodes cyprinus - Alec R. Lackmann; Ewelina S. Bielak-Lackmann; Reed I. Jacobson; Malcolm G. Butler; Mark E. Clark (Environmental Biology of Fishes, 2022)

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Trait-based approach reveals how marginal reefs respond to acute and chronic disturbance - B. Sommer; I. R. Butler; J. M. Pandolfi (Coral Reefs, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Compounds alone and in combination with yeasts to control Colletotrichum acutatum in apples - Kirsty S. H. Boyd-Wilson; Ruth C. Butler; Peter A. Alspach; Kerry R. Everett; I. P. Shamini Pushparajah; Monika Walter (Australasian Plant Pathology, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

The impacts of flooding on the high-latitude, terrigenoclastic influenced coral reefs of Hervey Bay, Queensland, Australia - I. R. Butler; B. Sommer; M. Zann; J.-x. Zhao; J. M. Pandolfi (Coral Reefs, 2013)

Sources of Botrytis cinerea inoculum for flower infection in blackcurrants in New Zealand - K. Boyd-Wilson; F. Obanor; R. C. Butler; P. Harris-Virgin; G. I. Langford; J. T. Smith; M. Walter (Australasian Plant Pathology, 2013)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Hyperglycemic oxoaldehyde, glyoxal, causes barrier dysfunction, cytoskeletal alterations, and inhibition of angiogenesis in vascular endothelial cells: aminoguanidine protection - Sean M. Sliman; Timothy D. Eubank; Sainath R. Kotha; M. Lakshmi Kuppusamy; Shariq I. Sherwani; Elizabeth Susan O’Connor Butler; Periannan Kuppusamy; Sashwati Roy; Clay B. Marsh; David M. Stern; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2010)

Biogeography of seed‐dispersal syndromes, life‐forms and seed sizes among woody rain‐forest plants in Australia's subtropics - D. W. Butler; R. J. Green; D. Lamb; W. J. F. McDonald; P. I. Forster (Journal of Biogeography, 2007)
Aim To enhance our understanding of the evolutionary interactions between seed‐dispersal syndromes, life‐forms, seed size, and habitat characteristics by studying their association with the regional‐scale distributions of subtropical rain‐forest plants in the context of climatic gradients. Location South‐east Queensland, subtropical eastern Australia (152° E, 26° S). Methods We classified 250 rain‐forest sites into six floristic site‐groups based on their woody plant composition. The resulting classification was strongly associated with variation in rainfall. The distribution of species across the floristic site‐groups was used to assign 568 species to seven habitat classes (one class for ‘widespread’ species, with all other species classified according to the site‐group within which they were most frequent). Species were also classified for three other categorical life‐history factors: three dispersal syndromes based on diaspore morphology (fleshy, wind‐assisted, and unadorned); four life‐forms (trees, shrubs and small trees, tall climbers, and short and shrubby climbers); and four seed‐diameter classes ( Results Across the rain forests of south‐east Queensland, the proportion of species with fleshy diaspores or of large stature increases with rainfall. High‐rainfall sites also have larger average seed sizes, but the difference in average seed size between high‐ and low‐rainfall sites is small compared with variation within sites. Among species, those with fleshy fruit tend to have larger seeds and to favour high‐rainfall sites. Very few small trees produce diaspores adapted for wind‐assisted dispersal. On average, species with unadorned diaspores have smaller seeds than those with fleshy diaspores. However, within sites, species with unadorned and fleshy diaspores have similar average seed sizes, and some species with unadorned diaspores from high‐rainfall habitats have extremely large seeds. Main conclusions Commonly observed associations between fleshy fruit, larger plants, larger seeds, and productive habitats are apparent within the rain‐forest flora of south‐east Queensland. However, these associations are generally weak and involve complex interactions. For example, the strong tendency for species with fleshy fruit to have larger seeds than those with unadorned diaspores concealed a significant group of species from wetter forests that produce extremely large seeds and unadorned diaspores. The most widespread species in this study tend to be large plants (particularly robust lianes) and to produce fleshy fruit, but they tend not to have relatively large seeds. The association between large seeds, large plants, fleshy fruit and productive habitats is discussed as part of an evolutionary strategy favouring fitness in populations close to carrying capacity. We review some problems with focusing on establishment chances per seed as the driver towards association between large seeds, large plants and productive rain‐forest habitats (the difficult‐establishment hypothesis). Instead we suggest that production of large, short‐lived seeds by long‐lived plants in temporally stable, closed habitats may reflect the limited evolutionary potential for strategies enhancing colonization (e.g. producing large numbers of dormant seeds), thus allowing the establishment benefits of large seeds greater selective influence (the slow‐replacement hypothesis). The association of fleshy fruit with large seeds probably reflects the difficulty of dispersing large seeds by other means (the difficult‐dispersal hypothesis).

Modelling the impacts of removing seal predation from Atlantic salmon, Salmo salar , rivers in Scotland: a tool for targeting conflict resolution - J. R. A. BUTLER; S. J. MIDDLEMAS; I. M. GRAHAM; P. M. THOMPSON; J. D. ARMSTRONG (Fisheries Management and Ecology, 2006)
Bioenergetics were used to model the potential impacts on adult Atlantic salmon, Salmo salar L., stocks and rod fisheries of removing harbour seals, Phoca vitulina L., from three rivers of different scales in the Moray Firth, Scotland, viz: the Spey (large), Conon (medium) and Moriston (small). Overall, seals had the greatest impact on the Moriston, where removal of a single animal could increase cumulative catch by 17% during the fishing season. On the Conon and Spey the impacts were negligible, and resulted in increased catches of 33% in rivers with monthly rod catches ≤10 fish, but declined to 34 fish. The outputs of the models are qualitative, but provide a management tool for targeting action to resolve seal‐salmon fishery conflict. Smaller salmon population units, and spring salmon sub‐stocks and fisheries in particular, are most vulnerable to predation. The merit of this approach is discussed regarding the management of Special Areas of Conservation for salmon and seals.

Some properties of adenylate kinase from chemolithotrophically grown Thiobacillus novellus - I. R. C. McKellar; A. M. Charles; B. J. Butler (Archives of Microbiology, 1980)